Analisis Kesiapan Sekolah dalam Penerapan Kurikulum Merdeka Di SMKN 1 Sei Menggaris (Sekolah 3T) - Zein, Nafisah (Proceedings Series of Educational Studies, 2024)
Abstract This research was conducted with school principals, vice principals or curriculum vice principals, and several teachers at SMKN 1 Sei Menggaris, Kab. Nunukan. This study used interview guidelines to analyze the data. The data analysis used was qualitative data analysis, which summarized the interview findings. Overall, we can say that we are ready to understand the characteristics and structure of the curriculum, develop lesson plans, and plan the implementation of teaching. The interview results correspond to the six indicators. However, there are shortcomings that need to be addressed, such as the readiness of instructional materials and modules, the readiness of facilities and infrastructure, and the readiness of assessment planning in teaching the independent curriculum. The purpose of this research is to determine the readiness of schools, especially in 3T schools (Frontier, Lagging, and Outermost), namely SMKN 1 Sei Menggaris. It is hoped that from the results of this research, schools can address issues that have not been well prepared and enable the independent curriculum at SMKN 1 Sei Menggaris to run optimally.